Augmenting thermo-hydro-chemical seed priming and germination dynamics on genotype/cultivar-Arka Shubra: a spineless green manure legume cover crop Mucuna pruriens L. DC. var. utilis - Alagowdanahalli Channakeshavegowda Jnanesha; Sunkari Ranjith Kumar; Sripathi Bharath Kumar; Sripathi Venu Gopal; Karre Sravya; Ashish Kumar; Raj Kishori Lal (Technology in Horticulture)
The exploration of seed priming techniques represents a critical avenue for enhancing agricultural productivity, particularly in leguminous cover crops like Mucuna pruriens L. DC. var. utilis is commonly known as the velvet bean. This spineless green manure legume has significant potential for sustainable agricultural systems, offering multiple ecosystem services including soil fertility improvement, erosion control, and nitrogen fixation. Over 2022–2023, an experiment was conducted to evaluate the impact of diverse seed treatments on the germination dynamics and seedling growth of trichomeless (spineless) Mucuna pruriens. The experiment was designed in an RCBD with three replications, occurred under shaded conditions. Various treatments were applied, including scarification, soaking in hot and normal water, H2SO4, KNO3 + HNO3, GA3, and thiourea. The results indicated that H2SO4 treatment significantly enhanced the germination rate (57.14% ± 2.49%) and reduced the mortality rate (42.86% ± 2.49%) compared with the other treatments. Additionally, the H2SO4 treatment exhibited higher values for VI I (2.91 ± 0.21) and VI II (51.18 ± 4.41) than the other treatments. Furthermore, the application of H2SO4 resulted in a greater seedling drying weight (0.90 ± 0.04 g) in comparison to other treatments, with GA3 showing similar trend at 0.82 ± 0.02 g. The observed PCA plot indicates that PC-1 and PC-2 collectively explained 96.17% of the total variation. These findings highlight the effectiveness of H2SO4 in promoting favorable germination and seedling growth characteristics in spineless Mucuna pruriens.